2017
DOI: 10.1371/journal.pone.0170015
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive RNA-Seq Profiling to Evaluate the Sheep Mammary Gland Transcriptome in Response to Experimental Mycoplasma agalactiae Infection

Abstract: Mycoplasma agalactiae is a worldwide serious pathogen of small ruminants that usually spreads through the mammary route causing acute to subacute mastitis progressing to chronic persistent disease that is hard to eradicate. Knowledge of mechanisms of its pathogenesis and persistence in the mammary gland are still insufficient, especially the host-pathogen interplay that enables it to reside in a chronic subclinical state. This study reports transcriptome profiling of mammary tissue from udders of sheep experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…In the past few years, the transcriptome has been widely analyzed using microarrays [ 24 – 28 ]. In recent years, however, next-generation sequencing (NGS) technology has been used to explore differentially expressed genes in the mammary gland tissue or milk under different physiological and pathological conditions [ 5 , 17 , 29 31 ]. This research has revealed that an abundance of genes plays a very complex and important role in the regulation of lactation and mammary gland tissue health.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, the transcriptome has been widely analyzed using microarrays [ 24 – 28 ]. In recent years, however, next-generation sequencing (NGS) technology has been used to explore differentially expressed genes in the mammary gland tissue or milk under different physiological and pathological conditions [ 5 , 17 , 29 31 ]. This research has revealed that an abundance of genes plays a very complex and important role in the regulation of lactation and mammary gland tissue health.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we compared the pathogen-mediated transcriptional responses in birds to those in mammals. We used 14 previously published studies that generated transcriptomes for control individuals and pathogen-challenged individuals to identify differentially expressed genes in response to pathogen infection for a species of mammal (Supplementary file 1 Table 11; (Qian et al, 2013; Langley et al, 2014; Ogorevc et al, 2015; Rojas-Peña et al, 2015; DeBerg et al, 2016; Lee et al, 2016; Tran et al, 2016; Chopra-Dewasthaly et al, 2017; de Jong et al, 2018). We chose studies that used similar pathogens as those used in the avian experiments to compare the expression profiles of the two clades as closely as possible, while acknowledging that such matching will necessarily be somewhat imprecise.…”
Section: Methodsmentioning
confidence: 99%
“…RNA‐seq (Wang, Gerstein, & Snyder, ) should also be exploitable to identify genes that are significantly up‐ or down‐regulated during interaction with host cells, or in planktonic versus biofilm lifestyles or during intracellular replication. Dual RNA‐seq approaches, whereby both pathogen and host transcriptional profiles are simultaneously delineated, should inform our understanding of host responses to infection, as has been recently applied to the host mammary response to the related pathogen M. agalactiae (Chopra‐Dewasthaly, Korb, Brunthaler, & Ertl, ). In the initial characterization of the host transcriptional responses in five tissues following intratracheal M. bovis administration, differential expression of 157–994 genes was detected (depending on tissue), with the BPIFA1 , C9 and CD14 genes identified as “key players” in the immune function networks (Behura et al., ).…”
Section: Gap Analysismentioning
confidence: 99%